Suitable rice (Oryza sativa) variety for rice–fish farming system in rainfed lowland ecosystem under organic nutrition - RAUTARAY, S K; SINHABABU, D P (The Indian Journal of Agricultural Sciences, 2012)
Field trials were conducted during 2003–07 to find out suitable rice varieties for rice-fish farming under organic nutrition in rainfed medium deepwater ecology at the experimental farm of Regional Rainfed Lowland Rice Research Station, Gerua, Assam. Among the rice varieties, highest grain yield (3.96 tonnes/ha) was recorded in Ranjit, followed by Durga, Piolee and Sarala. The combined direct and residual effect of kharif varieties on kharif rice-rabi rice sequence in terms of equivalent yield also revealed Ranjit as the best variety for kharif season followed by Durga and Piolee. In rabi season, long-duration variety Rupsundari performed better over the short-duration Vandana. Piolee showed better tolerance to natural submergence, which occurred for 10 days in 2004. Grain yield was highest (4.64 tonnes/ha) in the flood year due to inflow of nutrients (silt) with flood water. The fish yield was 472 kg/ha/10 months.